SLC5A2 mutations, including two novel mutations, responsible for renal glucosuria in Chinese families - Yu, Lei (BMC Nephrol, 2020)
BACKGROUND: Familial renal glucosuria (FRG) is characterized by persistent glucosuria without other impairments of tubular function in the presence of normal serum glucose. SGLT2, which is almost exclusively expressed in the kidney, accounts for most of the glucose reabsorption. Recently, some studies have confirmed that SLC5A2 mutations are responsible for the pathogenesis of familial renal glucosuria, but FRG cases are still rare. Furthermore, there are a few reports about splice-site mutations in previous studies, but the effect of these variants at the mRNA level has hardly been verified. METHODS: Ten patients were recruited in our renal division because of persistent glucosuria, and clinical data of the patients and their family members were recorded as much as possible. The entire coding region and adjacent intronic segments of SLC5A2 were sequenced in FRG patients and their relatives. Permanent growing lymphoblastoid cell lines from FRG patients were established to better preserve genetic information. RESULTS: A total of nine different mutations were identified: IVS1-16C > A, c.305C > T/p.(A102V), c.395G > A/p.(R132H), c.736C > T/p.(P246S), c.886(−10_-31)delGCAAGCGGGCAGCTGAACGCCC, c.1152_1163delGGTCATGCTGGC/p.(Val385_Ala388del), c.1222G > T/p.(D408Y), c.1496G > A/p.(R499H) and c.1540C > T/p.(P514S); two novel mutations in SLC5A2, c.1222G > T/p.(D408Y) and c.1496G > A/p.(R499H), were identified in the Chinese FRG pedigrees. Ten individuals with heterozygous or compound heterozygous variants had glucosuria in the range of 3.1 to 37.6 g/d. CONCLUSION: We screened ten additional Chinese FRG pedigrees for mutations in the SLC5A2 gene and found nine mutations, including two novel mutations. Most variants were private, but IVS1-16C > A and c.886(−10_-31) del may be high frequency splice-site mutations that could be preferentially screened when variants cannot be found in the SLC5A2 exon. Furthermore, we successfully established a permanent growing lymphoblastoid cell line from patients with FRG, which could facilitate further studies of the SLC5A2 gene. The current study provides a valuable clue for further research on the molecular mechanism of SGLT2.